Gambaran Praktik Public Speaking Santri Madrasah Aliyah Ma’had Al-Zaytun Tahun 2024 - Hafidah Ilmi Hasanah; Imang Maulana; Muhammad N. Abdurrazaq (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Public speaking is an essential skill that every individual, especially Madrasah Aliyah students, must master to prepare for societal challenges. This skill not only supports the ability to convey information effectively but also plays a crucial role in building self-confidence, enhancing communication competencies, and preparing students to contribute to community life. At MA Ma'had Al-Zaytun, public speaking is an integral part of the curriculum aimed at equipping students with skills relevant to real-world demands. This study aims to identify effective strategies to improve the public speaking skills of students at MA Ma’had Al-Zaytun by analyzing the factors influencing these skills within the context of pesantren education. The research adopts a qualitative approach, utilizing data collection techniques such as in-depth interviews, observations, and documentation. The findings indicate that the public speaking program, through activities such as muhadhorah, significantly contributes to enhancing students' confidence and communication abilities. However, challenges such as nervousness and lack of preparation remain issues to be addressed. These findings provide important implications for the development of more effective and adaptive public speaking training programs in pesantren and other educational institutions.